Hybrid collaborative business model: the missing link between ambidexterity and strategic business performances for SMEs / Hasvenda Noor Abd Rahim and Hasliza Abdul Halim - Abd Rahim, Hasvenda Noor; Abdul Halim, Hasliza (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
This study examines the relationship between organisational ambidexterity, hybrid collaborative business models, and strategic performance in Malaysian SMEs from the lens of the Extended Resource Based View (ERBV) theory. Drawing on interdisciplinary sources, a conceptual framework was developed to explore the determinants of SMEs strategic performance viewed from the standpoint of ambidexterity and collaborative business models.